MENGENDALIKAN LAJU KOROSI PADA CHASSIS MITSUBISHI FE 114 DENGAN VARIASI QUENCHING - -, Sudarsono (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Mitsubishi Chassis is steal that contains 0.044% Carbon. The limitation is especially on its corrosion resistance; therefore. The aim of the study was to know the effect of hardening on the process of quenching and tempering toward hardness, micro structure and corrosion resistance of Mitsubishi Chassis FE 114 to increase the age of material usage. This study used material of Mitsubishi chassis FE114 of truck vehicle. It was done heating by using furnace (heater oven) on temperature 850Â°C for about 30 minutes. After that it was quenched by using viscosity variation of oil media with number of viscosity SAE 50, SAE 90 and SAE 140. To know the material characteristics after quenching and tempering, it was done hardness, micro structure, and corrosion testing.The result of this study shows that the value of hardening of Mitsubishi Chassis FE 114 increases on tempering of the hardness about 160.431 BHN on specimen quenching with oil media SAE 50, SAE 90. On the observing of micro structure, heating on quenching process and continued by tempering 200Â° C for 30 minutes occurred on perlite and ferrite phases. The corrosion speed before quenching process is 46.39 mm/year. The resistance of corrosion decrease after doing quenching process for all viscosity variation oil media. This shows that corrosion resistance of Mitsubishi Chassis FE 114 can not be increased with quenching process.